2002
DOI: 10.1097/00055735-200212000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic, immunologic disorder that may affect multiple organ systems. Keratoconjunctivitis sicca is the most common ocular manifestation, but visual morbidity is usually due to retinal and neuro-ophthalmic manifestations of the disease. Ocular manifestations of lupus are a reflection of systemic disease. The presence of ocular manifestations should alert the clinician to the likely presence of disease activity elsewhere. Therefore, all patients with ocular lupus should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 43 publications
2
48
1
6
Order By: Relevance
“…The retinal signs often parallel the severity of systemic inflammation, and may indicate control of the systemic disease [69,70]. SLE retinopathy: There is a strong correlation between presence of retinopathy and central nervous system disease such as cerebrovascular attacks, dementia, seizure, chorea, and transverse myelopathy [71][72][73].…”
Section: Posterior Eye Segment Manifestationsmentioning
confidence: 99%
“…The retinal signs often parallel the severity of systemic inflammation, and may indicate control of the systemic disease [69,70]. SLE retinopathy: There is a strong correlation between presence of retinopathy and central nervous system disease such as cerebrovascular attacks, dementia, seizure, chorea, and transverse myelopathy [71][72][73].…”
Section: Posterior Eye Segment Manifestationsmentioning
confidence: 99%
“…1 The classic retinal findings are haemorrhages and cotton-wool spots and VA is generally unaffected. A rare form of retinopathy seen in patients with SLE is the so-called severe vaso-occlusive retinopathy.…”
Section: Commentmentioning
confidence: 99%
“…Previous studies indicated that inflammation, such as seen in systemic autoimmune diseases including Sjogren's syndrome and systemic lupus erythematosus, is a common manifestation of dry eye symptoms [4,5]. Some researchers have thus proposed to use topical or systemic immunomodulatory therapy in severe dry eye conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%